Strengthening the Romanian rural household by improving current demographic structures - Lorena Florentina Chiţea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The main purpose of this research was to establish measures to prevent demographic structural changes, which would positively influence the process of modernization-sustainable development of the rural household and the Romanian rural area. The starting point of the research was the creation of a typology of rural area modernization and socio-economic development from the point of view of the rural household modernization potential. To quantify the links between the investigated phenomena and the demographic indicators, the Pearson correlation was used, which highlighted the type of connection (direct, indirect or without influence). Based on this information, the research was completed by developing three scenarios - the optimistic, realistic and pessimistic scenarios - of consolidating the rural household by improving demographic structures. The demographic indicators taken into consideration registered a significant decline in the analysed period, except for the group of counties with net prospects for modernization- development, which emphasizes the need for demographic policies to prevent existing structural problems.
Keywords: R20; Q01; O2; 330; rural area; rural household; sustainable development